2022
DOI: 10.1021/acs.jpclett.1c03827
|View full text |Cite
|
Sign up to set email alerts
|

Borophane Polymorphs

Abstract: Hydrogenated borophenesborophaneshave recently been synthesized as a new platform for studying low-dimensional borides, but most of their lattice structures remain unknown. Here, we determine the structures of borophane polymorphs on Ag(111) by performing extensive structural search using the cluster expansion method augmented with first-principles calculations. Our results reveal rich borophane polymorphs whose stability depends on hydrogen pressure. At relatively low hydrogen pressures, borophane structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The layered structure of the as-synthesized borophane is clearly shown in Figure S6, and the atomic layer numbers of the borophane sheets can be up to 4. The thickness of monolayer borophane structure is theoretically 0.2 nm, and the distance between adjacent borophene layers was predicted to be around 0.3 nm, so the total thickness of the as-synthesized 4-layer borophane is around 1.7 nm, ,, which is in line with AFM results (Figures d and S4). A high-resolution TEM (HRTEM) image and the corresponding selected area electron diffraction (SAED) pattern indicate that the borophane has a good crystallinity (Figure c), and the lattice spacings ( d ) are approximately 3.0 ± 0.1 and 5.0 ± 0.1 Å (Figure c,d), which are consistent with those of previous theoretical and experimental β 12 -borophane (lattice constants: a = 3.0 ± 0.2 Å, b = 5.0 ± 0.2 Å, and γ = 90°). ,,,,, In addition, TEM images in another region also show the same result and further demonstrate the structure phase of the borophane (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…The layered structure of the as-synthesized borophane is clearly shown in Figure S6, and the atomic layer numbers of the borophane sheets can be up to 4. The thickness of monolayer borophane structure is theoretically 0.2 nm, and the distance between adjacent borophene layers was predicted to be around 0.3 nm, so the total thickness of the as-synthesized 4-layer borophane is around 1.7 nm, ,, which is in line with AFM results (Figures d and S4). A high-resolution TEM (HRTEM) image and the corresponding selected area electron diffraction (SAED) pattern indicate that the borophane has a good crystallinity (Figure c), and the lattice spacings ( d ) are approximately 3.0 ± 0.1 and 5.0 ± 0.1 Å (Figure c,d), which are consistent with those of previous theoretical and experimental β 12 -borophane (lattice constants: a = 3.0 ± 0.2 Å, b = 5.0 ± 0.2 Å, and γ = 90°). ,,,,, In addition, TEM images in another region also show the same result and further demonstrate the structure phase of the borophane (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to graphene that must inherit its lattice structure from graphite, borophene features structural diversity, manifested as a highly variable pattern of hollow hexagons in a reference triangular grid, thereby promising a substantial breadth of physical and chemical properties. Extensive theoretical and experimental studies have shown that borophene exhibits structural anisotropy, ,,, high in-plane elasticity, unprecedented bendability, substantial metallicity, ,,, distorted Dirac Fermions, visible range plasmonics, even phonon-mediated superconductivity , and controllable hydrogenation. However, borophene does not have its own fixed structure but depends on the epitaxial substrate. ,, It means that any synthesized borophene is given a lattice structure only pertaining to that substrate; if transferred, it has a propensity of undergoing structural reconstruction and instability upon, for example, thermal perturbation. For practical applications, it is important to obtain borophene with a lattice structure that is highly robust against variation in its environment.…”
mentioning
confidence: 99%
“…However, subsequent theoretical studies showed a preferential occupancy of the lower surface of β 12 sheet along the metal surface with high hydrogen coverage. 8 The focus was to effectively eliminate ambient oxidation by hydrogenating the borophene surface. The correlation of change in electron count upon hydrogenation to the structure is equally interesting.…”
mentioning
confidence: 99%